Application of Mannich bases to the synthesis of hydroxymethylated isoflavonoids as potential antineoplastic agents. Issue 46 (29th September 2015) - Frasinyuk, Mykhaylo S.; Mrug, Galyna P.; Bondarenko, Svitlana P.; Sviripa, Vitaliy M.; Zhang, Wen; Cai, Xianfeng; Fiandalo, Michael V.; Mohler, James L.; Liu, Chunming; Watt, David S.
Abstract : C-6 and C-8 Hydroxy-, acetoxy- and alkoxymethyl derivatives of isoflavones were synthesized from Mannich bases and show inhibition in the low micromolar range in a prostate cancer PC3 cell line. Abstract : The regiospecific Mannich aminomethylation of 7-hydroxyisoflavonoids using bis( N, N -dimethylamino)methane afforded C-8 substituted N, N -dimethylaminomethyl adducts, and the regioselective aminomethylation of 5-hydroxy-7-methoxyisoflavonoids afforded predominantly the C-6 substituted N, N -dimethylaminomethyl adducts. Acetylation of these C-6 or C-8 Mannich bases with potassium acetate in acetic anhydride provided access to the corresponding acetoxymethyl derivatives that were subsequently converted to hydroxymethyl- and methoxymethyl-substituted 5-hydroxy- or 7-hydroxyisoflavonoids related to naturally occurring flavonoids. The C-8 acetoxymethyl, hydroxymethyl or methoxymethyl-substituted isoflavonoids possessed promising inhibitory potency in the low micromolar range in a prostate cancer PC-3 cell proliferation assay.